Language Varieties and Translanguaging Among Students of High Socio-Economic Status - Aji Seno Suwondo; Erna Andriyanti; Ashadi Ashadi (Indonesian Journal of EFL and Linguistics, 2023)
The social status of speakers often influences the use of their languages, which might also reflect their sociocultural identity. This article aims to reveal the language varieties used by students from high social economic status (SES) and the use of translanguaging types they perform during their interactions with different people in their surroundings. Adopting a mix of content analysis and case study design, this study used observation on five high school students from high socio-economic backgrounds and from different school settings in public and private schools. The selection of these students followed a snowball technique, in which the research setting gatekeepers chose the suitable participants. The employment of different translanguaging types was then calculated in a tabulation form to reveal a pattern. The results show that Indonesian was used as the high variety while Javanese, English, and Japanese were used as the low variety. Their use of languages also shows the elaborate code as high SES normally use and identify as high SES they have. On the other hand, the most widely use type of translanguaging by students is interlingual translanguaging, which shows the frequency of interaction with foreign languages. Likewise, the use of figurative language was used as intersemiotic translanguaging when they communicated at home. These results build on existing evidence of the similarities of the goals and the environment will affect how they do interaction. Students with high socio-economic tend to maintain their identity through interlingual translanguaging. Eventually, they can interact with other students with the same goals to blend their social class or backgrounds directly. Therefore, the use of a proper and correct multi-linguistic strategy needs to be introduced.